1992
DOI: 10.1116/1.586037
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Eley–Rideal mechanism in the addition of hydrogen atoms to unsaturated hydrocarbons on Cu(111)

Abstract: The addition of hydrogen atoms to ethylene and benzene on a Cu(111) surface has been studied by temperature-programmed desorption and integrated desorption mass spectrometry. The results show that adsorbed ethylene and benzene react with atomic hydrogen from the gas phase at temperatures as low as 110 K. The reaction intermediates, ethyl groups and partially hydrogenated benzene, can be isolated on the surface at this low temperature. When the surface is heated to above 150 K, hydrogen elimination reactions oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 0 publications
4
71
0
Order By: Relevance
“…Previous studies by Bent and coworkers have shown that benzene adsorbs and desorbs molecularly on the Cu ( I I I ) surface (12). As for the close-packed Pt and Rh surfaces, the first monolayer of benzene adsorbs with the molecular plane parallel to the surface plane (12).…”
Section: Subject Terms Is Number Of Pagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by Bent and coworkers have shown that benzene adsorbs and desorbs molecularly on the Cu ( I I I ) surface (12). As for the close-packed Pt and Rh surfaces, the first monolayer of benzene adsorbs with the molecular plane parallel to the surface plane (12).…”
Section: Subject Terms Is Number Of Pagesmentioning
confidence: 99%
“…As for the close-packed Pt and Rh surfaces, the first monolayer of benzene adsorbs with the molecular plane parallel to the surface plane (12). From temperature-programmed desorption (TPD) of perdeutero (d6-) benzene on Cu{ 1 II) it is known that multilayer and monolayer coverages of benzene desorb from the surface below 250K.…”
Section: Subject Terms Is Number Of Pagesmentioning
confidence: 99%
“…18,19 It was reported that on Cu surface hydrogenation of acetylene with adsorbed atomic hydrogen is unlikely. 12 Intuitively, we could assume that styrene with an ethylene group is also less likely for hydrogenation on Cu(111) with adsorbed atomic hydrogen. In Figure 1, the 102 amu peak at 170 K is assigned to multilayer PA.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 For adsorbed ethylene and benzene on Cu(111), the adsorbed molecules more plausibly react with atomic hydrogen in gas phase than with adsorbed atomic hydrogen. 12 Selective hydrogenation reaction is also of very importance. Pd catalysts have been used for the removal of acetylene impurity from ethylene without forming ethane from ethylene, 13 Additionally, the selective hydrogenation of PA to styrene is of importance to obtain pure styrene without producing other products such as ethylbenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Assisted by temperature programmed desorption, X-ray and ultra-violet photoelectron spectroscopies, we have studied CH3I which has widely been a Deceased August 31,2007 employed for understanding (heterogeneous) catalytic photochemical and thermal reaction processes of halocarbons adsorbed on a metal substrate. [12][13][14][15][16][17] Because the initial thermal or photo-dissociation channel is a breakage of C-I bond, and no reformation of C-I bond occurs it is possible to separately elucidate the behaviors of CH3 and I.…”
Section: Introductionmentioning
confidence: 99%